2019
DOI: 10.1002/ijc.32386
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and reproductive factors and risk of esophageal and gastric cancer by subtype and subsite: Results from the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort

Abstract: Obesity has been associated with upper gastrointestinal cancers; however, there are limited prospective data on associations by subtype/subsite. Obesity can impact hormonal factors, which have been hypothesized to play a role in these cancers. We investigated anthropometric and reproductive factors in relation to esophageal and gastric cancer by subtype and subsite for 476,160 participants from the European Prospective Investigation into Cancer and Nutrition cohort. Multivariable hazard ratios (HRs) and 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 46 publications
2
34
3
1
Order By: Relevance
“…reproductive factors in women and oesophageal squamous cell carcinoma, ever having a still birth/miscarriage/termination was positively associated with this malignancy and an older age at first live birth and last live birth was inversely associated. Our study found a positive association between BMI and oesophageal adenocarcinoma among men, which is in line with previous cohort studies [32,33], but we found no statistically significant association for women, which is inconsistent with data from the Million Women's Study and the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort [34,35]. However, we had very few cases of oesophageal adenocarcinoma among women in this study (n = 48) and the test for interaction by sex was not statistically significant.…”
Section: Plos Onecontrasting
confidence: 83%
See 4 more Smart Citations
“…reproductive factors in women and oesophageal squamous cell carcinoma, ever having a still birth/miscarriage/termination was positively associated with this malignancy and an older age at first live birth and last live birth was inversely associated. Our study found a positive association between BMI and oesophageal adenocarcinoma among men, which is in line with previous cohort studies [32,33], but we found no statistically significant association for women, which is inconsistent with data from the Million Women's Study and the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort [34,35]. However, we had very few cases of oesophageal adenocarcinoma among women in this study (n = 48) and the test for interaction by sex was not statistically significant.…”
Section: Plos Onecontrasting
confidence: 83%
“…After adjustment for waist-to-hip ratio, the positive association between BMI and oesophageal adenocarcinoma in men was attenuated but remained statistically significant. The NIH-AARP study and EPIC study showed a non-significant positive association between BMI and oesophageal adenocarcinoma adjusted for waist-to-hip ratio [35,36]. Our study found a statistically significant positive association for gastric cardia cancer with BMI in men, but this association attenuated after adjustment for waist-to-hip ratio.…”
Section: Plos Onecontrasting
confidence: 55%
See 3 more Smart Citations